Muscle cramps and neuropathies in patients with allogeneic hematopoietic stem cell transplantation and graft-versus-host disease - Kraus, Peter D.; Jarius, Sven (PLOS ONE, 2012)
Objective Graft-versus-host disease (GVHD) is an immune-mediated multisystemic disorder and the leading cause of morbidity after allogeneic hematopoietic stem cell transplantation. Peripheral nervous system manifestations of GVHD are rare but often disabling. Whereas immune-mediated neuropathies are an established feature of GVHD, muscle cramps are not well characterized. Methods In a single-centre retrospective cohort we studied 27 patients (age 23 to 69 years) with GVHD (acute n = 6, chronic n = 21) who complained of symptoms suggestive of peripheral nervous system complications. Clinical, laboratory and neurophysiological findings were evaluated by descriptive statistics and regression analysis to detect factors associated with muscle cramps. Patient’s sera were examined for anti-neuronal antibodies. Results Nine patients had polyneuropathy, 4 had muscle cramps, and 14 had both. Median onset of polyneuropathy and muscle cramps was 6 and 9 months after allogeneic hematopoietic stem cell transplantation, respectively. Neurophysiology revealed a predominantly axonal polyneuropathy in 20 of 26 patients. In 4 of 19 patients electromyography showed signs of myopathy or myositis. Muscle cramps were more frequent during chronic than acute GVHD and affected muscles other than calves in 15 of 18 patients. They typically occurred daily, lasted 1 to 10 minutes with medium to severe pain intensity, compromised daily activity or sleep in 12, and were refractory to therapy in 4 patients. Muscle cramps were less likely with tacrolimus treatment and signs of severe polyneuropathy, but more likely with myopathic changes in electromyography and with incipient demyelinating polyneuropathy, shown by increased high frequency attenuation of the tibial nerve. Serological studies revealed antinuclear or antimitochondrial antibodies in a subset of patients. Two of 16 patients had a serum reactivity against peripheral nervous tissue. Conclusion Muscle cramps are associated with chronic GVHD, often compromise daily activity, and correlate negatively with axonal polyneuropathy and positively with myopathy and incipient demyelination.